2019
DOI: 10.1002/cbdv.201800543
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Materials Formed by Self‐Assembling Hydrophobic, Aromatic Peptides Dedicated to Be Used for Regenerative Medicine

Abstract: The aims of this study were to identify the short aromatic peptides which are able to form highly ordered amyloid‐like structures in self‐assembling processes, to test the influence of length of hydrophobic peptides on tendency to aggregation, and to check if aggregated peptides fulfill requirements expected for materials useful for scaffolding. All tested hydrophobic peptides were prepared on solid phase by using DMT/NMM/TsO− as a coupling reagent. The progress of aggregation was studied by set of independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The use of three independent methods has avoided the problem that the fact that methods of studying weak interaction, including self‐organization processes, are associated with a high risk of false results. This approach turned out to be useful in our search for fragments responsible for insulin aggregation as well as in research on the influence of aromatic amino acids on the ability to aggregate short peptides [45–49] . Results of microscopic examination of complexes formed by fragments of amylin (18–22) H‐HSSNN‐OH; (23–27) H‐FGAIL‐OH, (33–37) H‐GSNTY‐NH 2 prone to aggregation with fragments: cyclic (1–7) H‐KCNTATC‐OH, (8–12) H‐ATQRL‐OH, (13–17) H‐ANFLV‐OH, (28–32) H‐SSTNV‐OH devoid of aggregation properties are shown in Figures 3–5.…”
Section: Resultsmentioning
confidence: 99%
“…The use of three independent methods has avoided the problem that the fact that methods of studying weak interaction, including self‐organization processes, are associated with a high risk of false results. This approach turned out to be useful in our search for fragments responsible for insulin aggregation as well as in research on the influence of aromatic amino acids on the ability to aggregate short peptides [45–49] . Results of microscopic examination of complexes formed by fragments of amylin (18–22) H‐HSSNN‐OH; (23–27) H‐FGAIL‐OH, (33–37) H‐GSNTY‐NH 2 prone to aggregation with fragments: cyclic (1–7) H‐KCNTATC‐OH, (8–12) H‐ATQRL‐OH, (13–17) H‐ANFLV‐OH, (28–32) H‐SSTNV‐OH devoid of aggregation properties are shown in Figures 3–5.…”
Section: Resultsmentioning
confidence: 99%
“…After 7 days of incubation, a solution of CR in phosphate buffer and/or Thioflavin T was added to the samples. Standard procedures were followed [38–40] …”
Section: Resultsmentioning
confidence: 99%
“…Standard procedures were followed. [38][39][40] Five of the tested peptides were found to have an inhibitory effect on the aggregating (18)(19)(20)(21)(22) HÀ HSSNNÀ OH fragment ( Figure 5). No inhibitory effect was noted for HÀ F(NÀ Me)GA(NÀ Me)ILÀ OH (6) in a complex with (18-22) HÀ HSSNNÀ OH.…”
Section: Resultsmentioning
confidence: 99%
“…showed that the incorporation of one cysteine residue to the C‐terminal position in FF leads to nanospheres instead to typically observed fibers . In our previous study, we investigated the self‐assembling properties of several homomeric aromatic dipeptides (containing two identical residues) and of peptides with two identical aromatic residues and cysteine or methionine and we also found that incorporation of cysteine residue into peptide chain can change the morphology of aggregates.…”
Section: Introductionmentioning
confidence: 94%